Suppose √k is irrational and a, b, c and d are rational
if
a + b√k = c + d√k
then
a = c and b = d
Solve for x and y given that they are irrational.
Problem 1 :
x + y √2 = 5 - 6√2
Solution :
x + y √2 = 5 - 6√2
Comparing the corresponding terms, we get x = 5 and y = -6
Problem 2 :
(x + y√2)(3 - √2) = - 2√2
Solution :
(x + y√2)(3 - √2) = - 2√2
Using distributive property,
3x - x √2 + 3y √2 - y √2 √2 = -2√2
3x - x √2 + 3y √2 - 2y = -2√2
(3x - 2y) + √2(-x + 3y) = -2√2
By comparing the corresponding terms,
3x - 2y = 0 -----(1)
-x + 3y = -2 -----(2)
While solving the system of equation, we can get the values of x and y
(1) + 3(2)
3x - 3x - 2y + 9y = 0 - 6
7y = -6
y = -6/7
Applying the value of y in (2), we get the value of x.
-x + 3(-6/7) = -2
-x - (18/7) = -2
-x = -2 + (18/7)
-x = (-14 + 18)/7
-x = 4/7
x = -4/7
Problem 3 :
Find rationals a and b such that
(a + 2√2)(3 - √2) = 5 + b√2
Solution :
(a + 2√2)(3 - √2) = 5 + b√2
Using distributive property,
3a - a√2 + 3(2√2) - 2√2√2 = 5 + b√2
3a - a√2 + 6√2 - 4 = 5 + b√2
(3a - 4) + √2(-a + 6) = 5 + b√2
Comparing the corresponding terms,
3a - 4 = 5 ----(1)
-a + 6 = b -----(2)
From (1) 3a = 5 + 4 3a = 9 a = 9/3 a = 3 |
Applying the value of a, -3 + 6 = b b = 3 |
So, the value of and b are 3 and 3 respectively.
Problem 4 :
Write √(1/7) in the form k√7. Then find the value of k.
Solution :
Comparing the coefficient of √7, we get k = 1/7
Problem 5 :
(a + b√2)2 = 33 + 20√2, find the values of a and b.
Solution :
(a + b√2)2 = 33 + 20√2
Using the algebraic identity
(a + b)2 = a2 + 2ab + b2
a2 + 2ab√2 + b2 √22 = 33 + 20√2
a2 + 2ab√2 + 2 b2 = 33 + 20√2
a2 + 2b2 = 33 ----(1)
2ab = 20
ab = 10
b = 10/a
Applying the value of b in (1), we get
a2 + 2(10/a)2 = 33
a4 + 200 = 33a2
a4 - 33a2+ 200 = 0
Let a2 = t
t2 - 33t + 200 = 0
(t - 25) (t - 8) = 0
t = 25 and t = 8
a2 = 25 and a2 = 8
a = 5 and a = 2√2
When a = 5, b = 10/5 ==> 2
When a = 2√2, b = 2√2/5
Problem 6 :
(a + b√2)2 = 41 - 24√2, find the values of a and b.
Solution :
(a + b√2)2 = 41 - 24√2
Using the algebraic identity
(a + b)2 = a2 + 2ab + b2
a2 + 2ab√2 + b2 √22 = 41 - 24√2
a2 + 2ab√2 + 2 b2 = 41 - 24√2
a2 + 2b2 = 41 ----(1)
2ab = -24
ab = -12
b = -12/a
Applying the value of b in (1), we get
a2 + 2(-12/a)2 = 41
a4 - 288 = 41a2
a4 - 41a2- 288 = 0
Let a2 = t
t2 - 33t - 200 = 0
(t - 32) (t + 9) = 0
t = 32 and t = -9
a2 = 32 and a2 = -9 (not possible)
a = 4√2
When a = 4√2, b = -12/4√2 ==> -3/√2
May 21, 24 08:51 PM
May 21, 24 08:51 AM
May 20, 24 10:45 PM